Absence of epizootic hematopoietic necrosis virus (EHNV) in diseased rainbow trout (Oncorhynchus mykiss) from fish farms in the Peruvian highlands - Bautista D., Karen (2018)
The objective of the present study was to monitor the detection of the Epizootic Hematopoietic Necrosis virus (EHNv) in trouts (Oncorhynchus mykiss) in fish farms of the highlands of Peru. Samples were taken from 111 diseased fish (liver, spleen, anterior kidney) from fish farms in the regions of Ancash, Junín and Huancavelica, Peru. The tissue samples were processed immediately for bacterial isolation and another group of samples were stored at -196 °C for PCR. The DNA of each tissue was extracted by the Trizol method and then purified with silica membranes (PureLink Genomic DNA kit). The PCR was performed using the MCP-1 primers specific for the EHNv, following the methodology proposed by the OIE and with the commercial kit VetPCRTM EHNV Detection for confirmation. Bacterial isolation was carried out by culturing on TSA and Anacker- Ordal agar (Cytophaga agar) of each tissue, and the identification by Gram stain and bacterial biochemistry. The EHNv DNA was not detected indicating that the prevalence of the virus is less than 5% or it is not present in the sampled fish farms. Yersinia ruckeri and Aeromonas spp were isolated in all the samples, indicating that the cause of the disease and mortality present in the fish farms was due to the infection with these bacteria.